Transfection Of Difficult-To-Transfect Zebrafish (Danio rerio) ZF4 Cells Using Chemical Transfection and Nucleofection Method - Rizka Rahmana Putri; Christian Larbi Ayisi (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2023)
ABSTRACTTransfection is a powerful tool for introducing foreign DNA into target cells. Many kits and methods are offered to simplify the process of introducing foreign DNA into cells. ZF4 is a cell type derived from zebrafish that is difficult to transfect. The majority of studies involving transfection into cells require transfection efficiency 70%. Our research demonstrates transfection using 2 kinds of methods, namely chemical transfection using X-tremeGene HP and electroporation-based transfection using a nucleofector device which will later be called Nucleofection. Our results show that transfection using electricity (Nucleofection) provides better transfection efficiency than chemical transfection (X-tremeGene HP).Keywords: maxGFP, nucleofection, transfection, zebrafish (Danio rerio), ZF4 cells